Digital forensics trial graphics : teaching the jury through effective use of visuals - Sammons, John; Daniel, Lars (Lars E.); ScienceDirect eBooks (London, United Kingdom : Academic Press is an imprint of Elsevier, 2017)
This book helps digital forensic practitioners explain complex technical material to laypeople (i.e., juries, judges, etc.). The book includes professional quality illustrations of technology that help anyone understand the complex concepts behind the science.
GARR REYNOLDS: WHAT IS GOOD PRESENTATION DESIGN?CRAIG BALL'S POWER PERSUASION; INDEX; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; V; W; Z; Back Cover.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed March 22, 2017).
Elsevier
Keywords: Computer crimes -- Investigation; Electronic evidence; SOCIAL SCIENCE -- Criminology; Computer crimes -- Investigation; Electronic evidence; Electronic books